دراسة أوجه النقص والقصور في نظام العقود الإدارية لمشاريع التشييد في سورية (مجلة جامعة اللاذقية- سلسلة العلوم الهندسية, 2018)
Construction sector is going to be one of the main sectors during the upcoming reconstruction phase and one of the most important spending and contracting fields in it, and in the process of configuration and preparation for this phase an urgent need arises to modernize the legislative environment of the construction sector and especially those laws that control the public projects in Syria. This research aims to evaluate the administrative contracts system that control the public projects in Syria (The Unified Contracts System issued by Law 51 and the General Conditions Book issued by ordinance 450) in several main points, by highlighting the shortages and insufficiencies in them, and comparing them to their corresponding in the most prominent international construction contracts and indicating the extent of the difference and the variance with these contracts. The research found that the current administrative contracts system is unable to suit the requirements of the reconstruction phase and that it needs changing in the philosophy of codification, structure, detailing, risk allocation, and other matters in order to tackle the shortages and insufficiencies in it, and to keep pace with the international construction contracts and meet the requirements of the upcoming reconstruction phase projects. سيكون قطاع التشييد أحد القطاعات الرئيسية خلال مرحلة إعادة الإعمار المقبلة وأحد أهم مجالات الإنفاق والتعاقدات فيها، وفي إطار عملية التهيئة والإعداد لهذه المرحلة تبرز الحاجة الملحة لتحديث البيئة التشريعية والقانونية لقطاع التشييد وخاصة الناظمة لمشاريع الجهات العامة في سورية. يهدف هذه البحث إلى تقييم نظام العقود الإدارية الناظمة لمشاريع الجهات العامة في سورية (نظام العقود الموحد الصادر بالقانون 51 و دفتر الشروط العامة الصادر بالمرسوم 450) في عدد من النقاط الرئيسية، وذلك من خلال تسليط الضوء على أوجه النقص والقصور الموجودة فيها، ومقارنتها مع ما يقابلها في أبرز عقود التشييد العالمية وتبيان مدى الاختلاف والتباين مع هذه العقود. وتوصل البحث إلى أن نظام العقود الحالي غير قادر على ملاءمة متطلبات مرحلة إعادة الإعمار وأنه بحاجة إلى تغيير يطال فلسفة التقنين والهيكلية والتفصيل وتوزيع المخاطر وغيرها من الأمور، وذلك لمعالجة أوجه النقص والقصور الموجودة فيه، ولمواكبة عقود التشييد العالمية وتلبية متطلبات مشاريع مرحلة إعادة الإعمار المقبلة.